The Relationship between E-Journal Use and User's Discipline: A Descriptive Study - Hülya Dilek Kayaoğlu (Türk Kütüphaneciliği)
The main purpose of this study is to examine the effect of discipline as an explanatory factor on e-journal use in the Istanbul University context. In order to meet this goal, the data used in this study were collected by a web based user survey conducted to examine the e-journal use of Istanbul University Faculty between the dates of October 2005 and February 2006. The results revealed that discipline was statistically significantly associated with both the 'frequency of use' and 'format preferences'. The results also suggest that the availability of e-journals might be a factor of the e-journal use.